2015
DOI: 10.1016/j.fct.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deoxynivalenol (DON) contaminated feed on intestinal integrity and immune response in swine

Abstract: This study was performed to characterize the influence of consuming DON naturally contaminated feeds on pig's intestinal immune defenses, antibody response and cellular immunity. Sixteen 4-week-old piglets were randomly allocated to two dietary treatments: control diet or diet contaminated with 3.5 mg DON/kg. At days 7 and 21, animals were immunized with ovalbumin (OVA). On day 42, intestinal samples were collected for measurement of gene expression involved in immune response, oxidative status and barrier fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 46 publications
8
59
1
2
Order By: Relevance
“…In the current experiment, an upregulation of claudins, CLDN-1, -3 and -4, was observed in the cecum of DON-fed piglets, while in the jejunum, the mRNA expression of different TJ proteins (OCLN, ZO-1 and ZO-2) is downregulated. Recently, Lessard et al [ 49 ] also showed a down-regulation in mRNA expression of CLDN-3, -4 and OCLN in the ileum of piglets fed a DON diet (3.5 mg /kg feed) for 42 days compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiment, an upregulation of claudins, CLDN-1, -3 and -4, was observed in the cecum of DON-fed piglets, while in the jejunum, the mRNA expression of different TJ proteins (OCLN, ZO-1 and ZO-2) is downregulated. Recently, Lessard et al [ 49 ] also showed a down-regulation in mRNA expression of CLDN-3, -4 and OCLN in the ileum of piglets fed a DON diet (3.5 mg /kg feed) for 42 days compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Attentions have focused on mycotoxins for their infection on monocotyledon-based crops such as maize, wheat and barley [ 1 ] which leads to economic losses of animal food production worldwide. In addition, mycotoxins decreased porcine growth performance, immune function, and reproductive performance [ 2 ]. Moreover, this well-known xenobiotic is capable to severely damage intestinal health by disrupting intestinal barrier, increasing intestinal permeability, inducing inflammatory responses to human intestinal epithelial cells (IEC S ) and intensifying the systemic inflammation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…DON has become an issue of major concern because it elicits toxic effects in humans as well as in animals [4,5]. Among various animal species, the pig is the most affected by DON and is considered the most relevant animal model of human sensitivity [6,7,8,9]. The gastrointestinal tract represents the first barrier against contaminated food and feed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro and in vivo studies have confirmed that this compound affects IEC function by modulating the proliferation and viability of cells and impairing intestinal barrier functions [12,13,14]. In addition, emerging evidence suggests that DON is directly involved in the inflammation of the intestine [9,15] and inhibits the absorption of nutrients via this organ [16]. It has been reported that phosphorylation of mitogen-activated protein kinases (MAPKs) plays a crucial role in the regulation of downstream events [7,12].…”
Section: Introductionmentioning
confidence: 99%